Penerapan Terapi Menggambar untuk Mengontrol Halusinasi Pendengaran pada Pasien ODGJ - Sodik Fitulah; Aprida Manurung; Bangun Dwi Hardika (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
Hallucinations are one of the symptoms of mental disorders in individuals which are characterized by sensory perception changes, namely feeling false sensations in the form of sounds, sight, tasting, touching or smelling. The application of drawing therapy in patients with auditory hallucination disorder may reduce hallucinogenic stimuli. The goal is to apply and analyze Nursing Care in Patients with Mental Disorders with the implementation of the application of drawing therapy to control auditory hallucinations. The method used in this is descriptive analysis with a case study approach. This study describes the application of drawing therapy to reduce the signs and symptoms of auditory hallucinations. It was also carried out by providing an intervention to apply drawing therapy for 15 minutes every day to three respondents for 7 consecutive days. The application of drawing therapy to the three respondents obtained results in the reduction of hallucinations from a moderate hallucinatory level score (22) to a mild level with a score (9). Brother B experienced a decrease in hallucinations from a moderate hallucination level score (20) to no hallucinations on days 6 and 7 with a score of (0). Brother JS decreased from a moderate hallucination level of score (20) to no hallucination on day 7 with a score of (0). It is hoped that the results of this study can provide an understanding of the application of drawing therapy to control auditory hallucinations.